Increased claudin‐3, ‐4 and ‐18 levels in bronchoalveolar lavage fluid reflect severity of acute lung injury. Issue 4 (25th April 2013) - Jin, Wenting; Rong, Linyi; Liu, Yinkun; Song, Yuanlin; Li, Yan; Pan, Jue
Abstract Background and objective Acute lung injury (ALI) is characterized by disruption of lung epithelial and endothelial cells, leading to increased membrane permeability and loss of barrier function. Claudins are key components of tight junctions (TJ) that regulate paracellular permeability, and play an important role in alveolar epithelial barrier function and fluid clearance. However, whether claudin‐3, ‐4, ‐18 or ‐5 expression changes in Pseudomonas aeruginosa (PA)‐induced ALI and the clinical significance of such change is unknown. Methods Rats underwent intratracheal instillation of PA, and samples were collected prior to and 3, 9 and 24 h after instillation. Lung injury was evaluated by bronchoalveolar lavage fluid (BALF) total protein, arterial blood gas analysis, lung injury score, and expression of surfactant protein and von Willebrand factor. Claudin expression in lung was measured with quantitative real‐time polymerase chain reaction and western blotting, and in BALF by enzyme‐linked immunosorbent assay. The relationship between claudins in BALF and lung injury grade were analysed with Spearman's rank correlation. Alveolar epithelium, endothelium and TJ ultrastructure were observed with electron microscopy. Results Claudin‐4, ‐18 and ‐5 mRNA levels increased significantly 24 h after PA instillation in the most severe lung injury cases, whereas there was no significant change in protein levels. Claudin‐3, ‐4 and ‐18 levels in BALF increased most 24 h after PA instillation; this paralleled alveolar epithelial disruption and lung injury severity. Conclusions Claudin‐3, ‐4 and ‐18 released into the alveolar compartment is highly associated with barrier function loss caused by alveolar epithelial injury.